The Effect of Company Growth, Dividend Policy, Leverage, Capital Intensity On Accounting Conservatism - Nathania Santosa; Nunung Aini Rahmah (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2026)
Objective – This research aims to obtain empirical evidence about the effects of Company Growth, Dividend Policy, Leverage, and Capital Intensity on Accounting Conservatism. Design/Methodology/Approach – This research adopts a quantitative approach. The sample comprises 18 Energy sector companies listed on the Indonesia Stock Exchange (IDX) over the period 2019-2023. To examine the proposed hypotheses, the study employs panel data regression analysis, utilizing Eviews 9 Software for the estimation and testing procedures. Findings – The results of this study found that Company Growth has a positive but statistically insignificant effect on Accounting Conservatism. Similarly, Leverage has a positive but statistically insignificant effect on Accounting Conservatism. In contrast, Capital Intensity has positive and significant effect on Accounting Conservatism. However, Dividend Policy has a negative and statistically insignificant effect on Accounting Conservatism. This study has certain limitations, as the Adjusted R-Square accounts for only 0,3% of the variation, suggesting that other factors outside the research model may affect Accounting Conservatism. Originality/Value – This research discusses Accounting Conservatism and other factors such as Company Growth, Dividend Policy, Leverage and Capital Intensity which focuses on energy sector companies. The research employs the Conservatism Accounting (CONACC) model as a measure of Accounting Conservatism. Future researchers are encouraged to employ alternative indicators beyond those used in this study in order to provide a more comprehensive understanding of Accounting Conservatism. Keywords – Company Growth, Dividend Policy, Leverage, Capital Intensity, Accounting Conservatism